2018
DOI: 10.1590/0104-6632.20180354s20170537
|View full text |Cite
|
Sign up to set email alerts
|

Golden Apple Cherry Snail Shell as Catalyst for Heterogeneous Transesterification of Biodiesel

Abstract: Calcium oxide catalysts prepared from golden apple cherry snail shell (Pomacea canaliculata) via two steps-deproteination and calcination-were compared: the structure was characterized by XRD and XRF and morphology by SEM. In addition, the effects of reaction time, catalyst loading amount, methanol:oil molar ratio and reaction temperature on the biodiesel yield were measured. The optimum conditions for biodiesel production, 0.8 wt% catalyst loading, 12:1 methanol:oil molar ratio, 65 OC reaction and 6 h reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 32 publications
3
19
0
Order By: Relevance
“…This observation was in line with what was earlier reported that catalyst basic strength decreases due to continuous intermediate products monoglyceride and diglyceride resulted as a result of the reaction, which obstructed the catalyst holes. The formation of water to oxygen reaction that occurred at the catalyst surface also reduces the catalyst sensitivity (Trisupakitti et al, 2017;Adepoju et al, 2020a;Adepoju et al, 2020c) [16,24,25].…”
Section: Brunauer-emmett-teller (Bet) and Xrd Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This observation was in line with what was earlier reported that catalyst basic strength decreases due to continuous intermediate products monoglyceride and diglyceride resulted as a result of the reaction, which obstructed the catalyst holes. The formation of water to oxygen reaction that occurred at the catalyst surface also reduces the catalyst sensitivity (Trisupakitti et al, 2017;Adepoju et al, 2020a;Adepoju et al, 2020c) [16,24,25].…”
Section: Brunauer-emmett-teller (Bet) and Xrd Analysismentioning
confidence: 99%
“…In the work of Balajii et al (2020) [13], the heterogeneous catalyst was made from the Banana peduncle, meanwhile, Minakshi et al (2020) [14] used Carica papaya stem as a bio-based catalyst. Further study by Hadiyanto et al (2016) [15] utilized Anadara granosa as a heterogeneous CaO-based catalyst, but, Trisupakitti et al (2019) [16] used golden apple cherry snail as a heterogeneous catalyst to synthesized biodiesel from the vegetable. Falowo et al (2020) [17] developed a new base catalyst from a combination of biomass wastes.…”
Section: Introductionmentioning
confidence: 99%
“…In the work of Balajii et al [13], the heterogeneous catalyst was made from the Banana peduncle, meanwhile, Minakshi et al [14] used Carica papaya stem as a bio-based catalyst. Further study by Hadiyanto et al [15] utilized Anadara granosa as a heterogeneous CaO-based catalyst, but, Trisupakitti et al [16] used golden apple cherry snail as a heterogeneous catalyst to synthesized biodiesel from the vegetable. Falowo et al [17] developed a new base catalyst from a combination of biomass wastes.…”
Section: Introductionmentioning
confidence: 99%
“…This observation was in line with what was earlier reported that catalyst basic strength decreases due to continuous intermediate products monoglycerideand diglyceride resulted as a result of the reaction, which obstructed the catalyst holes. The formation of water to oxygen reaction that occurred at the catalyst surface also reduces the catalyst sensitivity[16,24,25].…”
mentioning
confidence: 99%
“…In the work of Balajii et al (2020) [13], the heterogeneous catalyst was made from the Banana peduncle, meanwhile, Minakshi et al (2020) [14] used Carica papaya stem as a bio-based catalyst. Further study by Hadiyanto et al (2016) [15] utilized Anadara granosa as a heterogeneous CaO-based catalyst, but, Trisupakitti et al (2019) [16] used golden apple cherry snail as a heterogeneous catalyst to synthesized biodiesel from the vegetable. Falowo et al (2020) [17] developed a novel mesoporous base catalyst synthesis from a mixture of three agro-wastes.…”
Section: Introductionmentioning
confidence: 99%